PERLINDUNGAN HAK KONSUMEN TERHADAP MARAKNYA MONOPOLI BISNIS - Desta Adinda Rahmadhani; Sakirman . (Siyasah Jurnal Hukum Tatanegara, 2022)
In every company, consumer trust is a top priority. The Consumer Protection Law is one of the important things that must be known, so that in the future we will not be deceived or feel harmed by an item or thing that is purchased and consumed. To protect consumers from fraudulent competition, consumers need to get legal protection. Legal protection that can be provided are: preventive legal protection and repressive legal protection. The purpose of this paper is to determine the form of legal protection for consumers due to unfair competition. The conclusion obtained is that the form of preventive legal protection has been established by the government, namely with the establishment of Law Number 8 of 1999 concerning Consumer Protection and forms of repressive legal protection, carried out by litigation and non-litigation. Litigation settlement is carried out in court and non-litigation with the National Consumer Protection Agency, Non-Governmental Consumer Protection Agency, and Consumer Dispute Settlement Agency.